2012
DOI: 10.1186/1556-276x-7-363
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ambient humidity on the electrical properties of graphene oxide films

Abstract: We investigate the effect of water adsorption on the electrical properties of graphene oxide (GO) films using the direct current (DC) measurement and alternating current (AC) complex impedance spectroscopy. GO suspension synthesized by a modified Hummer's method is deposited on Au interdigitated electrodes. The strong electrical interaction of water molecules with GO films was observed through electrical characterizations. The DC measurement results show that the electrical properties of GO films are humidity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(99 citation statements)
references
References 26 publications
(37 reference statements)
7
92
0
Order By: Relevance
“…These ionic species dramatically enhanced the ionic conductivity and sharply increased the capacitance. [ 35,36 ] The impedance spectrum obtained from the GO-based humidity sensor could be modeled by an electrical equivalent circuit that included a single charge transfer resistance ( R ct ) value and two constant phase elements, CPE 1 and CPE 2 , as shown in Figure S2a in the Supporting Information. The impedance of a constant phase element ( Z CPE ) is defi ned…”
Section: Communicationmentioning
confidence: 99%
“…These ionic species dramatically enhanced the ionic conductivity and sharply increased the capacitance. [ 35,36 ] The impedance spectrum obtained from the GO-based humidity sensor could be modeled by an electrical equivalent circuit that included a single charge transfer resistance ( R ct ) value and two constant phase elements, CPE 1 and CPE 2 , as shown in Figure S2a in the Supporting Information. The impedance of a constant phase element ( Z CPE ) is defi ned…”
Section: Communicationmentioning
confidence: 99%
“…To investigate the synchronous vibration, Eqs. (35) and (36) should be used. Similar procedure to asynchronous vibration is used to calculate the frequencies, noting that u ¼ w ¼ 0 thus the interaction between the two nanoplates does not affect the frequency of the nanoplates, i.e., the synchronous frequencies are not dependent on the stiffness modulus K 0 unlike the asynchronous ones.…”
Section: Synchronous Vibrationmentioning
confidence: 99%
“…The effects of temperature and moisture on the dynamic failure responses of laminated graphite epoxy composites subjected to high strain rate loading were investigated by Wosu et al [35]. Yao et al [36] illustrated the effect of water adsorption on the electrical properties of graphene oxide films using experimental measurements. They found that, at low humidity, graphene exhibit poor conductivity, whereas at high humidity, the conductivity of graphene increases.…”
mentioning
confidence: 99%
“…Although GO has been known since the year 1855 [11], a heightened interest in GO was triggered by the explosion in graphene research started ago [12,13]. During the past five years, many research journals have reported the favorable properties of GO in various sensing applications with different designs such as direct measurement of capacitance between two parallel plates or in a slightly more complex CMOS architecture where the GO acts as insulating layers in the capacitor [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%